Evaluation of the Decree of the Minister of Environment and Forestry Number 17 of 2018 concerning Procedures for Release of Forest Areas and Changes in Forest Area Boundaries for Land Resources for Agrarian Reform Objects in Riau Province - Rizky, Rizky Setiawan; Rosyadi, M.Irfan; Yulanda, Mela; Rizky, Mutiara Miftahul (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
Indonesia has a forest area of around 94.1 million hectares which consists of various spatial functions including those used as Production Forests. Production forests which are currently used are around 63 million ha of Indonesia's forest area which is divided into permanent production forest areas, limited production forests. , and convertible production forests (HPK). In accordance with the policies contained in the Agrarian Reform Object Land (TORA) program issued by the central government, HPK is one of the targets used for area release. The current phenomenon that is occurring is that TORA does not accommodate land issues that previously had property rights issued by the National Land Agency which then turned into Convertible Production Forests. So far, what has arisen regarding land issues is the land mafia, but in this phenomenon the community is harmed again by changes in areas where the land with property rights status cannot be cultivated and bought and sold. This research will be carried out in Riau province with the National Land Agency and the Riau Provincial Forest Service as objects. The aim of this research is to resolve disputes over land issues, not only TORA, but also people who previously had land rights issued by BPN, changing their status to HPK. The method and type of this research is Qualitative Descriptive. The technique for attracting informants uses a proportional sampling technique and data collection techniques in this research are interviews, observation, literature study and documentation.